Photoinduced self-cleaning high-flux high-adhesion oil-water separation membrane and preparation method thereof

By in-situ growth of LDHs on the oil-water separation membrane and plasma modification treatment, a photo-induced self-cleaning high-flux and high-adhesion oil-water separation membrane was prepared, which solved the problems of membrane susceptibility to contaminant accumulation and insufficient adhesion, and achieved efficient, stable oil-water separation performance and long life.

CN121198075APending Publication Date: 2025-12-26CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511401307.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

Existing oil-water separation membranes are prone to flux reduction and insufficient adhesion due to the accumulation of water pollutants after long-term use, making it difficult to maintain high-efficiency separation performance in the separation of complex oil-in-water emulsions.

Method used

Metal-polyphenol porous coordination polymers (PCPs) are formed by using metal alkoxides and polyphenols, and layered double metal hydroxides (LDHs) are grown in situ on their surface. Combined with plasma modification treatment, a photo-induced self-cleaning high-flux and high-adhesion oil-water separation membrane is prepared.

Benefits of technology

It achieves high flux, superhydrophilicity, and superoleophobicity underwater, and has the ability to self-clean under light, which improves the service life and antifouling performance of the membrane, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121198075A_ABST
    Figure CN121198075A_ABST
Patent Text Reader

Abstract

The invention discloses a light-induced self-cleaning high-flux high-adhesion oil-water separation membrane and a preparation method thereof, the method comprises the following steps: S1, preparing a metal-polyphenol porous coordination polymer suspension, and drying to obtain a metal-polyphenol porous coordination polymer solid; s2, divalent metal nitrate polyhydrate, trivalent metal nitrate polyhydrate and PCP are mixed in water, alkali liquor is dropwise added to adjust the pH to be neutral, LDHs grow on the surface of a PCP solid in situ, and LDHs-PCP is obtained; s3, performing plasma treatment on the substrate filter membrane; and S4, dispersing LDHs-PCP in water, and carrying out suction filtration on the dispersion liquid onto the plasma modified substrate filter membrane to obtain the light-induced self-cleaning high-flux high-adhesion oil-water separation membrane. The oil-water separation membrane disclosed by the invention has high flux, super-hydrophilicity and underwater super-oleophobicity; the oil-water separator has high mechanical strength and illumination self-cleaning capability, and can stably operate for a long time in a high-strength oil-water separation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of separation membrane technology, and in particular to a photo-induced self-cleaning high-flux, high-adhesion oil-water separation membrane and its preparation method. Background Technology

[0002] With the acceleration of industrialization and urbanization, the discharge of oily wastewater has increased dramatically. Direct discharge of untreated oily wastewater will cause serious pollution to the aquatic environment. Compared with traditional water treatment technologies, membrane separation technology has become a hot research area due to its significant advantages such as high separation efficiency, small footprint, and ease of operation. Among these, membrane materials prepared based on the superwetting theory have received considerable attention in the field of oil-water separation in recent years due to their opposite wettability to oil and water, enabling efficient two-phase separation through filtration. For water-in-oil emulsions with a predominantly aqueous phase, developing separation membranes that combine superhydrophilic-underwater superoleophobic properties with micron-scale pore structures has become an important research direction in this field.

[0003] The core of high-performance superhydrophilic emulsion separation membranes lies in four key elements: high surface energy, high roughness, suitable mass transfer channels, and strong adhesion to the substrate membrane. Although numerous studies have effectively mitigated clogging caused by membrane fouling through strategies such as constructing special surface morphologies and designing oil- and water-oriented transport channels, the abundant polar groups and adsorption sites on the hydrophilic membrane surface make it highly susceptible to adsorbing water-soluble organic pollutants during separation. This adsorption not only alters the chemical properties of the membrane surface, leading to a decrease in underwater oleophobicity, but also significantly restricts its sustainable application in the separation of complex oil-in-water emulsions. For example, CN119708592A discloses a PDMAPAA@TA-APTES@PVDF composite hydrogel membrane, its preparation method, and its application. By forming a hydration layer and micro / nano structures on the membrane surface, it can prevent oil and other pollutants from directly contacting and adhering to the membrane surface, forming an effective "fouling resistance" barrier. However, this does not address the problem of increasing pollutant accumulation at the source. Over time, the accumulation of pollutants will inevitably reduce the performance of the final oil-water separation membrane.

[0004] Layered bimetallic hydroxides (LDHs), as a class of functional materials possessing both suitable bandgap width and surface roughness control capabilities, offer a novel pathway for constructing superwettable membranes due to their unique intercalation structure, which allows water molecules to enter the interlayer and form a stable hydration layer. Introducing semiconductor materials with suitable bandgap widths into oil-water separation membrane preparation can endow the membrane material with photoresponsive self-cleaning capabilities. When the contaminated membrane material is placed under light, the semiconductor absorbs light energy and triggers electron-hole pair separation, thereby driving the redox reaction of pollutants and achieving efficient degradation of pollutants on the membrane surface. However, LDHs still face challenges in practical applications: LDHs typically have poor compatibility with commercial membranes and are difficult to grow on them.

[0005] CN116943453B reports an oil-water separation membrane based on a metal polyphenol network and a layered bimetallic hydroxide, and its preparation method. The membrane utilizes a metal polyphenol network and a layered bimetallic hydroxide to construct a dual oil-resistant barrier on the surface of the filter membrane substrate, which alleviates the clogging of the membrane pores by oil. However, it still suffers from low water flux. Furthermore, after prolonged use, insufficient adhesion between the surface hydrophilic membrane material and the substrate membrane leads to the shedding of the surface hydrophilic membrane material, resulting in the loss of its original capabilities. Summary of the Invention

[0006] To overcome the technical problems of reduced flux and insufficient mechanical adhesion of oil-water separation membranes due to pollutant accumulation in water, this invention provides a photo-induced self-cleaning, high-flux, high-adhesion oil-water separation membrane and its preparation method. A metal-polyphenol porous coordination polymer (PCP) with high surface energy, high roughness, and suitable mass transfer channels is formed by using metal alkoxide compounds as chelating agents and coordinating with the phenolic hydroxyl groups of polyphenolic compounds. Layered double metal hydroxides (LDHs) are then grown in situ on the solid surface of the metal-polyphenol porous coordination polymer, endowing it with photo-induced self-cleaning functionality.

[0007] To solve the above-mentioned technical problems, the technical solution proposed by this invention is as follows:

[0008] The first aspect of this invention provides a method for preparing a photo-induced self-cleaning, high-flux, high-adhesion oil-water separation membrane, comprising the following steps:

[0009] S1. Prepare aqueous solutions of metal alkoxide compounds and polyphenol compounds. Add the aqueous solution of polyphenol compounds dropwise to the aqueous solution of metal alkoxide compounds to form a metal-polyphenol porous coordination polymer suspension. Centrifuge, wash, and dry to obtain a solid metal-polyphenol porous coordination polymer (PCP).

[0010] S2. Mix the polyhydrated divalent metal nitrate, the polyhydrated trivalent metal nitrate and the metal-polyphenol porous coordination polymer solid obtained in step S1 in water, and add alkaline solution to adjust the pH to neutral. Stir at room temperature to allow layered bimetallic hydroxides (LDHs) to grow in situ on the surface of the metal-polyphenol porous coordination polymer solid. Wash and dry to obtain the metal-polyphenol porous coordination polymer (LDHs-PCP) with in situ grown layered bimetallic hydroxides.

[0011] S3. The substrate filter membrane is degreased, dried, and subjected to plasma treatment to obtain a plasma-modified substrate filter membrane.

[0012] S4. Disperse the metal-polyphenol porous coordination polymer (LDHs-PCP) of the in-situ grown layered bimetallic hydroxide obtained in step S2 in deionized water, and filter the dispersion onto a plasma-modified substrate filter membrane to obtain a photo-induced self-cleaning high-flux high-adhesion oil-water separation membrane.

[0013] Preferably, the molar ratio of the metal alkoxide compound, the polyphenol compound, the hydrated divalent metal nitrate, and the hydrated trivalent metal nitrate is 1:0.5-1.5:0.5-6:0.5-6, and the molar ratio of the hydrated divalent metal nitrate to the hydrated trivalent metal nitrate is 1:1.

[0014] Preferably, in step S1, the metal alkoxide compound is at least one of zirconium n-propoxide, tetrabutyl titanate, Pd(PPh3)4, Et2Zn, and ferrocene.

[0015] Preferably, in step S1, the polyphenolic compound is at least one of kaempferol, tannic acid, luteolin, catechin, and p-hydroxybenzoic acid.

[0016] Preferably, since metal alkoxide compounds are easily hydrolyzed, a hydrolysis stabilizer is usually added to the preparation of the aqueous solution of the metal alkoxide compound, and the amount of the stabilizer is 5-20 wt% of the aqueous solution of the metal alkoxide compound.

[0017] Preferably, the hydrolysis stabilizer is an organic amine compound, and the organic amine compound is at least one of triethanolamine (TEA), diethanolamine (DEA), monoethanolamine (MEA), and triethylamine (TEA).

[0018] Preferably, the concentrations of both the aqueous solution of the metal alkoxide compound and the aqueous solution of the polyphenol compound are 0.5-5 wt%.

[0019] Preferably, the substrate filter membrane is any one of polytetrafluoroethylene (PTFE) membrane, nylon membrane, polypropylene (PP) membrane, polyethersulfone (PES) membrane, cellulose acetate (CA) / cellulose nitrocellulose (CN) membrane, polyvinylidene chloride (PVDC) membrane, and polyvinylidene fluoride (PVDF) membrane. It should be noted that the PVDF membrane is used as an example in this embodiment of the invention, and it should be understood that other membranes also have equivalent technical effects.

[0020] Preferably, the specific process of plasma modification is as follows: the ratio of oxygen to nitrogen is 3:1, the flow rate is 20-30 sccm, the plasma power is 80-120W, and the processing time is 8-15 minutes.

[0021] Preferably, the areal density of the in-situ grown layered bimetallic hydroxide metal-polyphenol porous coordination polymer solid on the substrate filter membrane is 0.01-10 mg / cm³.2 Within.

[0022] Preferably, the band gap of the layered bimetallic hydroxides (LDHs) is in the range of 1.5-3 eV.

[0023] In a second aspect, the present invention also provides a photo-induced self-cleaning high-flux, high-adhesion oil-water separation membrane prepared by the above-described preparation method.

[0024] In this invention, porous coordination polymers (PCPs), as a type of crystalline material constructed from metal ions and organic ligands, possess characteristics such as strong structural designability and excellent interfacial adhesion. They combine hydrophilicity and strong adhesion, achieving a robust bond between LDH nanosheets and the polymer substrate while preserving micron-level mass transfer channels. Compared to physical mixing of PCP and LDHs, LDHs grown in situ on PCP exhibit stronger contact forces, endowing the oil-water separation membrane with higher physical defense capabilities and extending its service life. Compared to PCP, which lacks light-based self-cleaning capabilities, the composite material of LDHs and PCP has the ability to degrade pollutants in water, further improving the service life of the oil-water separation membrane.

[0025] Plasma pretreatment was performed on the PVDF membrane. High-energy particles (electrons and ions) in the plasma bombarded the PVDF surface, breaking the CF and CC bonds and introducing hydroxyl (-OH), carboxyl (-COOH), or amino (-NH2) groups. These active groups can form hydrogen bonds or covalent bonds (such as ester bonds and amide bonds) with hydroxyl groups (such as metal oxide catalysts) and amino groups (such as organic catalysts) on the catalyst surface. These newly added chemical functional groups may form coordination bonds, hydrogen bonds, or even covalent bonds with LDHs-PCP materials, thereby greatly improving the adhesion ability of LDHs-PCP to the substrate membrane.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] (1) The photo-induced self-cleaning high-flux and high-adhesion oil-water separation membrane prepared by the present invention has high flux, superhydrophilicity, and underwater superoleophobicity; it has relatively high mechanical strength. Due to the use of in-situ growth technology, it grows in situ on PCP, which is different from ordinary LDHs, giving the separation membrane a certain physical defense capability and improving its service life.

[0028] (2) It has the ability to self-clean under light, and can decompose the pollutants attached to the surface in time after being exposed to light, thus improving its service life.

[0029] (3) The preparation method of the present invention uses plasma modification technology, which makes the adhesion between LDHs-PCP and the substrate PVDF membrane stronger, and can operate stably during long-term, high-intensity oil-water separation.

[0030] (4) The preparation method of the present invention is simple and environmentally friendly. The prepared oil-water separation membrane has superhydrophilic properties and excellent anti-fouling properties, making it suitable for industrial production and having a good application prospect in the field of oil-water separation. Attached Figure Description

[0031] Figure 1 A schematic diagram illustrating the synthesis and application of LDHs-PCP modified PVDF filter membrane.

[0032] Figure 2 Fourier transform infrared spectrum of LDHs-PCP modified PVDF filter membrane.

[0033] Figure 3 The XRD pattern of LDHs-PCP.

[0034] Figure 4 Optical profilometer results for the original PVDF filter membrane and the LDHs-PCP modified PVDF filter membrane.

[0035] Figure 5 Water contact angle of the original PVDF filter membrane and the LDHs-PCP modified PVDF filter membrane (a) and underwater oil contact angle of the LDHs-PCP modified PVDF filter membrane (b).

[0036] Figure 6 Emulsion before separation (a) and filtrate before separation (b) under an optical microscope (c).

[0037] Figure 7 This shows the particle size distribution of the emulsion and filtrate.

[0038] Figure 8 The effect of self-cleaning on wettability.

[0039] Figure 9 Adsorption and degradation experiments were conducted on pure metal-coordinated polyphenol compounds (Pure M-TAPCP) and pure hydrotalcite-like compounds (Pure LDHs).

[0040] Figure 10 Scanning electron microscope (SEM) images of the original polyvinylidene fluoride (PVDF) membrane (a), polyphenol porous coordination polymer (PCP) membrane (b), and layered double hydroxide polyphenol porous coordination polymer composite (LDHs-PCP) membrane (c). Atomic force microscope (AFM) images of the original PVDF membrane (d), polyphenol porous coordination polymer (PCP) membrane (e), and layered double hydroxide polyphenol porous coordination polymer composite (LDHs-PCP) membrane (f). Elemental distribution diagram of titanium (g), iron (h), and zinc (i) in the coating.

[0041] Figure 11 The permeation flux represents the permeation flux in different embodiments.

[0042] Figure 12 The residual LDHs-PCP on the membranes after rinsing with pure water for 48 h and 96 h was measured using plasma-modified LDHs-PCP composite PVDF membranes and unmodified LDHs-PCP composite PVDF membranes.

[0043] Image content description

[0044] Figure 1 The schematic diagram illustrates the synthesis process of the LDHs-PCP membrane, and also demonstrates the membrane's oil-water separation and light-induced self-cleaning capabilities.

[0045] Figure 2 This demonstrates the successful synthesis of the target metal-polyphenol porous coordination polymer. Detailed Implementation

[0046] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below in conjunction with the contents of the specification and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.

[0047] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0048] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0049] Example 1

[0050] A method for preparing a photo-induced self-cleaning, high-flux, high-adhesion oil-water separation membrane, such as... Figure 1 As shown, it includes the following steps:

[0051] S1. Preparation of Metal-Polyphenol Porous Coordination Polymer (PCP) Solid: First, a 1 wt% tetrabutyl titanate solution was prepared using a 1:10 mixture of triethanolamine (TEOA) and ethanol as solvents. This solution was continuously stirred magnetically at 300 rpm. Then, a 1.2 wt% tannic acid solution was prepared using a 1:2 mixture of water and ethanol as solvents. This solution was sonicated for 1 min to fully dissolve the tannic acid and transferred to a separatory funnel. It was then added dropwise to the tetrabutyl titanate solution at a rate of 1 mL / s. The volume ratio of tetrabutyl titanate solution to tannic acid solution was 2:1. After the addition was complete, stirring was continued for 5 min. The product, along with the solution, was then collected in a centrifuge tube, centrifuged, washed multiple times, and dried to obtain the metal-polyphenol porous coordination polymer (PCP) solid.

[0052] S2. Preparation of solid metal-polyphenol porous coordination polymer (LDHs-PCP) from in-situ growth of layered bimetallic hydroxides: 7.575 g Zn(NO3)2·6H2O and 4.04 g Fe(NO3)3·9H2O, along with the metal-polyphenol porous coordination polymer (PCP) obtained in S1, were completely dissolved or uniformly dispersed in 100 mL distilled water. The pH was controlled by titration with NaOH solution (2M). The mixture was stirred at room temperature for 18 h to form LDH with a molar ratio of 4:1. The solid product was filtered and washed several times with distilled water. The resulting LDHs-PCP was dried overnight in an oven at 80 °C.

[0053] S3. The substrate filter membrane is degreased, dried, and subjected to plasma treatment to obtain a plasma-modified PVDF membrane: A PVDF microfiltration membrane with a thickness of 100-200 μm (pore size 0.22-0.45 μm) is selected and cut into 10 cm x 10 cm pieces. The membrane pieces are soaked in anhydrous ethanol for 30 minutes to remove surface oil, then dried for later use. A low-frequency plasma treatment instrument (power range 0-500 W, frequency 13.56 MHz) is used. A quartz stage is placed inside the reaction chamber, and the pretreated PVDF membrane pieces are laid flat on the stage, ensuring a smooth, wrinkle-free surface. A working gas (a mixture of oxygen and nitrogen, volume ratio 3:1) is introduced, with a gas flow rate controlled at 20-30 sccm. The pressure in the reaction chamber is maintained at 10-30 Pa for 3 minutes. The plasma power is set to 80-120 W, and the treatment time is 8-15 minutes. During the treatment, the chamber temperature is kept below 60℃ (controlled by a water cooling system). Turn off the plasma power supply, continue to supply working gas for 30 seconds, and then stop the gas supply. A plasma-modified PVDF membrane is obtained.

[0054] S4. Place a 5cm diameter plasma-modified polyvinylidene fluoride (PVDF) circular filter membrane on a vacuum filtration device. Dilute 30mg of LDHs-PCP solid with an appropriate amount of deionized water and perform ultrasonic oscillation. Then filter the membrane on a vacuum device to obtain a photo-induced self-cleaning high-flux high-adhesion oil-water separation membrane (LDHs-PCP modified PVDF membrane).

[0055] Figure 2 The Fourier transform infrared spectrum shows the presence of a 3291 cm⁻¹. -1 1625cm -1 1346cm -1 828cm -1 and 667cm -1 Five absorption peaks. Among them, the peak at 3291 cm⁻¹ is the largest. -1 The absorption at this point originates from the stretching vibration of the hydroxyl (OH) bond and can be attributed to the phenolic and hydroxyl groups in tannins and LDHs. (1625 cm⁻¹) -1The absorption at 1346 cm⁻¹ originates from the vibration of the benzene ring skeleton. -1 The absorption at this point originates from the stretching vibration of the carbon-oxygen bond (CO), both attributed to tannic acid. 828cm -1 The absorption at that point is CO3 2- The characteristic peak originates from the anions in the LDH layers. 667 cm⁻¹ -1 The absorption at this point comes from the stretching vibration of the titanium-oxygen bond (Ti-O), which is a reaction product of tetrabutyl titanate and tannic acid.

[0056] Figure 3 The XRD pattern confirms the successful synthesis of the target LDHs-PCP.

[0057] Example 2

[0058] The difference between Example 2 and Example 1 of this invention is that the metal elements of the LDHs prepared in step S2 are changed from Zn and Fe to Co and Al. Specifically, in step S2, 7.275g of Co(NO3)2·6H2O, 3.86g of Al(NO3)3·9H2O, and the metal-polyphenol porous coordination polymer (PCP) obtained in step S1 are completely dissolved or uniformly dispersed in 100mL of distilled water, and the pH value is controlled by titration with NaOH solution (2M). The mixture is stirred at room temperature for 18h to form LDHs with a molar ratio of 4:1. The solid product is filtered and washed several times with distilled water.

[0059] Example 3

[0060] The difference between Example 3 and Example 1 of the present invention is that the surface density of the LDHs-PCP modified PVDF membrane prepared in step S4 is 0.5 mg / cm³. 2 .

[0061] Example 4

[0062] The difference between Example 4 and Example 1 of the present invention is that the surface density of the LDHs-PCP modified PVDF membrane prepared in step S4 is 5 mg / cm³. 2 .

[0063] Comparative Example 1

[0064] The difference between Comparative Example 1 and Example 1 of the present invention is that the LDHs in step S2 are prepared in advance and then physically mixed with PCP, rather than growing LDHs in situ on the PCP surface.

[0065] The specific steps are as follows: 7.575g Zn(NO3)2·6H2O and 4.04g Fe(NO3)3·9H2O were completely dissolved in 100mL of distilled water, and the pH value was controlled by titration with NaOH solution (2M). The mixture was stirred at room temperature for 18h to form ZnFe-LDHs with a molar ratio of 4:1. The solid product was filtered and washed several times with distilled water. The metal-polyphenol porous coordination polymer (PCP) obtained in S1 was then completely dissolved or uniformly dispersed with ZnFe-LDHs in 100mL of distilled water. The physically mixed LDHs-PCP was dried overnight in an oven at 80℃.

[0066] Comparative Example 2

[0067] The difference between Comparative Example 2 and Example 2 of the present invention is that the PVDF in S3 was not subjected to plasma treatment.

[0068] Comparative Example 3

[0069] The difference between Comparative Example 3 and Example 1 of the present invention is that the areal density of the LDHs-PCP modified PVDF membrane prepared in step S4 is 0.05 mg / cm³. 2 .

[0070] Comparative Example 4

[0071] The difference between Comparative Example 4 and Example 1 is that the surface density of the LDHs-PCP modified PVDF membrane prepared in step S4 is 50 mg / cm³. 2 .

[0072] The high-throughput, high-adhesion oil-water separation membranes prepared in the above embodiments and comparative examples, as well as the substrate PVDF membrane (blank control), were applied to oil-water separation experiments:

[0073] The samples to be separated included several laboratory-prepared simulated emulsions and one real emulsion derived from an industrial process. In preparing the emulsions, oil and water were mixed at a ratio of 1:99, and 100 mg / L was added. -1 Sodium dodecyl sulfonate was used as the surfactant. The cutter head of the high-speed emulsifier was placed in the oil-water mixture, with the cutter head flush with the liquid surface. Emulsification consisted of a 4000 rpm process and a 2500 rpm process, each lasting 5 minutes. The oils used included cyclohexane, kerosene, and pump oil. Kerosene was used as the primary test material. Emulsion separation was performed on a cross-flow filtration device with a constant transmembrane pressure of 0.15 bar. The separation permeability was calculated as follows:

[0074]

[0075] Where ΔV(L) is the filtrate volume, and A(m 2Δt(h) is the effective filtration area, Δp(bar) is the filtration time, and Δt(bar) is the transmembrane pressure. The cross-flow filtration device is connected to a computer, which monitors and records the current filtrate quality in real time, automatically calculates permeability, and generates a time-permeability curve. The separation efficiency is calculated as follows:

[0076]

[0077] Where C0 and C1 represent the oil content of the emulsion and filtrate, respectively, in mg·L⁻¹. -1 The oil content was detected using an infrared oil content analyzer.

[0078] After preparing the oil-in-water emulsion as described above, methylene blue was added to achieve a concentration of 1 mg / L. Dead-end filtration was used, with each separation consisting of 50 mL. The absorbance before and after separation was recorded using a UV-Vis spectrophotometer. The procedure for each photo-induced self-cleaning process was as follows: the membrane containing the adsorbed contaminants was placed in a beaker filled with water, magnetic stirring was turned on, and the membrane was irradiated with a 500W mercury lamp for 5 minutes.

[0079] Depend on Figure 4 It can be seen that the average roughness Ra increased from 0.963 μm to 3.148 μm, while the root mean square roughness Ra increased from 1.198 μm to 3.752 μm. According to the Wenzel model in wettability theory, increasing the surface roughness can further amplify the hydrophilicity and underwater oleophobicity of the hydrophilic / underwater oleophobic surface, which is beneficial to enhancing the oil-water separation performance of the modified PVDF membrane.

[0080] Depend on Figure 5 It can be seen that, compared with the original PVDF membrane (blank control), the PVDF membrane modified by the metal-polyphenol porous coordination polymer (PCP-LDHs) of layered double metal hydroxide has a smaller water contact angle, a larger oil contact angle, and stronger anti-oil adhesion properties, and has superhydrophilic and underwater superoleophobic properties.

[0081] Depend on Figure 6 It can be seen that the oil-water emulsion to be treated becomes clearer after passing through the PCP-LDHs modified oil-water separation membrane, indicating that the PCP-LDHs modified PVDF membrane has oil-water separation capability. Figure 7 It can be seen that after the oil-water emulsion to be treated passes through the PCP-LDHs modified oil-water separation membrane, the oil droplet size changes from the micron level to the nano level, resulting in strong oil-water separation capability.

[0082] Depend on Figure 8It is known that the pure metal-polyphenol porous coordination polymer PVDF membrane has a strong adsorption capacity for pollutants, so the pollutant concentration initially decreases rapidly, but then stops decreasing over time. In contrast, LDHs do not have good adsorption capacity, so the pollutant concentration does not initially decrease, but it gradually decreases after light exposure, indicating successful pollutant degradation. This demonstrates that the PCP-LDHs modified PVDF membrane has good photoinduced self-cleaning properties.

[0083] Figure 9 It can be demonstrated that the PCP-LDHs modified PVDF membrane possesses underwater superoleophobic properties and photo-induced self-cleaning properties. As shown in the figure, the initial underwater contact angle of the PCP-LDHs modified PVDF membrane is greater than 150°, indicating its underwater superoleophobic properties. After fouling, the oleophobic properties decreased, but after photo-induced self-cleaning, the underwater contact angle recovered to greater than 150°, indicating that the pollutants had been degraded.

[0084] Figure 10 It can be clearly seen that the original PVDF filter membrane has a porous structure with a smooth pore surface and no rough structure. However, the PVDF membrane modified with Ti-TAPCP and LDHs in Example 1 has a large number of particles on its surface, with obvious nanostructure and layering, and its roughness is improved.

[0085] The permeation flux of Example 1 and the comparative example are as follows: Figure 11 As shown, in-situ growth technology has better throughput than physical mixing.

[0086] Figure 12 The figures show the residual LDHs-PCP on the LDHs-PCP-modified PVDF membrane in Example 1 and the LDHs-PCP-modified PVDF membrane in Comparative Example 2 after rinsing with pure water for 48 hours and 96 hours. It can be seen that the oil-water separation membrane after plasma modification has better interlayer adhesion and a longer service life.

[0087] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. However, it should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a photo-induced self-cleaning, high-flux, high-adhesion oil-water separation membrane, characterized in that, Includes the following steps: S1. Prepare aqueous solutions of metal alkoxide compounds and polyphenol compounds, then add the aqueous solution of polyphenol compounds dropwise to the solution of metal alkoxide compounds to form a metal-polyphenol porous coordination polymer suspension. Centrifuge, wash, and dry to obtain a solid metal-polyphenol porous coordination polymer. S2. Mix the polyhydrated divalent metal nitrate, the polyhydrated trivalent metal nitrate and the metal-polyphenol porous coordination polymer solid obtained in step S1 in water, add alkaline solution dropwise to adjust the pH to neutral, stir at room temperature, and grow layered bimetallic hydroxide in situ on the surface of the metal-polyphenol porous coordination polymer solid. Wash and dry to obtain the metal-polyphenol porous coordination polymer with in situ grown layered bimetallic hydroxide. S3. The substrate filter membrane is subjected to degreasing, drying and plasma modification treatment to obtain a plasma-modified substrate filter membrane. S4. Disperse the metal-polyphenol porous coordination polymer of the in-situ grown layered bimetallic hydroxide obtained in step S2 in water, and filter the dispersion onto a plasma-modified substrate filter membrane to obtain a photo-induced self-cleaning high-flux high-adhesion oil-water separation membrane.

2. The method for preparing the photo-induced self-cleaning high-flux, high-adhesion oil-water separation membrane according to claim 1, characterized in that, The molar ratio of the metal alkoxide compound, the polyphenol compound, the hydrated divalent metal nitrate, and the hydrated trivalent metal nitrate is 1:0.5-1.5:0.5-6:0.5-6, and the molar ratio of the hydrated divalent metal nitrate to the hydrated trivalent metal nitrate is 1:1; preferably, the metal alkoxide compound is at least one of zirconium propoxide, tetrabutyl titanate, Pd(PPh3)3, Et2Zn, and ferrocene.

3. The method for preparing the photo-induced self-cleaning high-flux, high-adhesion oil-water separation membrane according to claim 1, characterized in that, In step S1, the polyphenolic compound is at least one of kaempferol, tannic acid, luteolin, catechin, and p-hydroxybenzoic acid.

4. The method for preparing a photo-induced self-cleaning, high-flux, high-adhesion oil-water separation membrane according to claim 1, characterized in that, The aqueous solution of the metal alkoxide compound also includes a hydrolysis stabilizer, which has a content of 5-20 wt% in the aqueous solution of the metal alkoxide compound.

5. The method for preparing the photo-induced self-cleaning high-flux, high-adhesion oil-water separation membrane according to claim 4, characterized in that, The hydrolysis stabilizer is an organic amine compound, and the organic amine compound is at least one of triethanolamine, diethanolamine, monoethanolamine, and triethylamine.

6. The method for preparing the photo-induced self-cleaning high-flux, high-adhesion oil-water separation membrane according to claim 1, characterized in that, The concentrations of the aqueous solutions of the metal alkoxide compound and the polyphenol compound are both 0.5-5 wt%.

7. The method for preparing the photo-induced self-cleaning high-flux, high-adhesion oil-water separation membrane according to claim 1, characterized in that, The substrate filter membrane is any one of polytetrafluoroethylene membrane, nylon membrane, polypropylene membrane, polyethersulfone membrane, cellulose acetate / cellulose nitrate membrane, polyvinylidene chloride membrane, and polyvinylidene fluoride.

8. The method for preparing the photo-induced self-cleaning high-flux, high-adhesion oil-water separation membrane according to claim 1, characterized in that, In step S4, the specific process of plasma treatment is as follows: the ratio of oxygen to nitrogen introduced is 3:1, the flow rate is 20-30 sccm, the plasma power is 80-120W, and the treatment time is 8-15 minutes.

9. The method for preparing the photo-induced self-cleaning high-flux, high-adhesion oil-water separation membrane according to claim 1, wherein the areal density of the in-situ grown layered bimetallic hydroxide metal-polyphenol porous coordination polymer solid on the substrate filter membrane is 0.5-5 mg / cm³. 2 Within.

10. The photo-induced self-cleaning high-flux high-adhesion oil-water separation membrane prepared by the method of any one of claims 1-9.

Citation Information

Patent Citations

  • PDMAPAA-coated TA-APTES-coated PVDF composite hydrogel film and preparation method and application thereof

    CN119708592A